Are YouTube™ videos a reliable source of information about temporomandibular joint arthrocentesis? - Muhammet Bahattin Bingül; Mehmet Emrah Polat (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Arthrocentesis is a very common method of joint-space lavage for temporomandibular joint disorders. This study evaluated the content and quality of YouTube™ videos on temporomandibular joint arthrocentesis as a source of information for patients, using a sample of 80 videos. Purpose: The goal of this study was to analyze popular YouTube™ videos associated with temporomandibular joint arthrocentesis and to evaluate their accuracy and quality. Methods: The authors searched for the keywords “temporomandibular joint arthrocentesis” on YouTube™ and filtered the first 80 videos by number of views; the 42 videos that met the inclusion criteria were evaluated. Each video was scored between 0 and 8 and categorized as containing poor, moderate, or excellent content. When evaluating the results, the significance level was set at 5%: p<0.05 for a significant difference and p>0.05 for no significant difference. Results: The quality of 61.9% of the evaluated videos was moderate. Some 38.1% of the videos contained poor information content. Evaluated by target group, videos targeting health professionals were more effective in terms of content than videos targeting only lay people (p=0.005), but there was no difference in the interaction and viewership data. Conclusion: YouTube™ may currently be providing patients with misleading content about arthrocentesis. However, YouTube™ videos may affect patients’ decisions. Videos should therefore be checked before they are posted.